FTMP-based Approach toward Dislocation Dynamics of PSB - S Ihara; N Kojima; T Hasebe (International Journal of Multiphysics, 2021)
This study targets dynamic behavior of interacting dislocations associated with PSB (Persistent Slip Bands) ladder structures, ultimately responsible for fatigue crack initiations, based on FTMP (Field Theory of Multiscale Plasticity), applied to simulation results by dislocation dynamics. Focus is place on the stable/unstable of the dislocation systems in terms of FTMP-based incompatibility tensor field in particular via the attendant phase-space trajectories (PhS-Ts). The stable responses are shown to be manifested as the limit-like loci on the PhS-Ts, whereas the unstable responses mainly due to cross slip-driven vacancy-type debris loop generations are specifically represented by the incompatibility rate, i.e., the quantity well correlate the frequency of the debris loop formations. The incompatibility rate, used here as the ordinate of the PhS-Ts, can be interpreted as the creation/annihilation rate of edge dislocation pairs, in the FTMP-based context, which corroborates the correlation result.